(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2022)
This study is on psychological profiling of artisans(motor mechanic, hair dressers, panel beaters, and tailors) on emotional intelligence, attitude to work, self efficacy and locus of control. In this study eight hypotheses were tested, four were confirmed and four were rejected. The study used 220 participants who are artisans in the ikotun area of Lagos state. 50 were mechanics (males) 40 were hair dressers (females) 30 were panel beaters (males) and 100 tailors (50 males/50 females). Their age range is between 15 and 50 years. It was a survey in which cluster random sampling was used. T.Test for independent groups was used to analyze the data.